Tissue Resources for the Functional Annotation of Animal Genomes - Tixier-Boichard, Michèle; Fabre, Stéphane; Dhorne-Pollet, Sophie; Goubil, Adeline; Acloque, Hervé; Vincent-Naulleau, Silvia; Ross, Pablo; Wang, Ying; Chanthavixay, Ganrea; Cheng, Hans; Ernst, Catherine; Leesburg, Vicki; et al. (Frontiers in Genetics, 2021)
In order to generate an atlas of the functional elements driving genome expression in domestic animals, the FAANG strategy was to sample many tissues from a few animals of different species, sexes, ages, and production stages. This paper presents the collection of tissue samples for four species produced by two pilot projects, at INRAE and UC Davis (UCD). There were three mammals (cattle, goat, and pig) and one bird (chicken). It describes the metadata characterizing these reference sets (1) for animals with origin and selection history, physiological status and environmental conditions (2) for samples with collection site and tissue/cell processing (3) for quality control (4) for storage and further distribution. Three sets are identified: set 1 comprises tissues which collection can be standardized and for which representative aliquots can be easily distributed (liver, spleen, lung, heart, fat depot, skin, muscle and PBMC); set 2 comprises tissues requiring special protocols because of their cellular heterogeneity (brain, digestive tract, secretory organs, gonads and gametes, reproductive tract, immune tissues, cartilage); set 3 comprises specific cell preparations (immune cells, tracheal epithelial cells). Dedicated sampling protocols were established and uploaded on https://data.faang.org/protocol/samples. Specificities between mammals and chicken are described when relevant. A total of 73 different tissues or tissue sections were collected and 21 are common to the four species. Having a common set of tissues will facilitate the transfer of knowledge within and between species and will contribute to decrease animal experimentation. Combining data on the same samples will facilitate data integration. Quality control was performed on some tissues with RNA extraction and RNA quality control. More than 5000 samples have been stored with unique identifiers and more than 4000 were uploaded onto the Biosamples database, provided that standard ontologies were available to describe the sample. Many tissues have already been used to implement FAANG assays, with published results. All samples are available without restriction for further assays. The requesting procedure is described. Members of FAANG are encouraged to apply a range of molecular assays to characterize the functional status of collected samples and share their results, in line with the FAIR data principles.